Indices of Household Welfare and the Value of Leisure Time - Kokoski, Mary F. (The Review of Economics and Statistics, 1987)
Abstract-Leisure-inclusive welfare indices, such as the real wage index, have been previously investigated only with aggregate data. Using micro data, however, these indices show the effects of increasing labor market employment of household members. Real wage, expenditure, and nonlabor income indices are compared across six types of husband/wife households. These indices are also compared to ad hoc real wage and leisure-exclusive index measures. Doubt is cast on past results based upon aggregate data. I.